MAKNA KEHARMONISAN KELUARGA BAGI PASANGAN SUAMI ISTRI DI STASI SANTO PAULUS DATAI NIRUI PAROKI SANTA MARIA DE LA SALETTE MUARA TEWEH - Michael Chelvin Oktovino Yandeng; Silvester Adinuhgra; Paulina Maria Ekasari Wahyuningrum (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2019)
This study aims to understand, describe and analyze the meaning of family harmony based on the field research with a focus of research that leads to 1) understand about families from the married couples in St. Paulus Datai Nirui, 2) describe the meaning of family harmony according to the couples at St. Paulus Datai Nirui, 3) analyze factors that cause disharmony in the household, 4) describe married couples expectations for further family life. The research method used is a qualitative approach. Data collection techniques are done by interview and documentation. Data analysis techniques using interactive patterns with stages performed 1) gathering information from the field, 2) Select information through themes that have been sorted and presented using Indonesian, 3) Drawing conclusions. The research was carried out on June 8-22 at the St. Paul Datai Nirui Station in the Parish of Santa Maria de la Salette Muara Teweh. There were 11 informants interviewed consisting of 5 married couples and 1 parish priest.